2019
DOI: 10.26466/opus.547217
|View full text |Cite
|
Sign up to set email alerts
|

Stresle Çift Olarak Baş Etme Envanteri’nin Türkçe’ye Uyarlanması

Abstract: ÖzBu çalışmanın amacı Bodenmann (2008) tarafından geliştirilen Stresle Çift Olarak Baş Etme Envanteri'nin Türkçe'ye uyarlanmasıdır. Bu amaç doğrultusunda yapılan bu araştırma, Adana ilinde özel kuruluş ve devlet kurumlarında çalışan 720 evli ve çocuk sahibi bireyden toplanan veriler ile gerçekleştirilmiştir. Uyarlama kapsamında önce çeviri çalışmaları tamamlanmış olup, ardından envanterin Türkçe formunun geçerlik ve güvenilirliği incelenmiştir. Envanterin yapı geçerliğini belirlemek için doğrulayıcı faktör ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Dyadic Coping Inventory (DCI) This scale was developed originally by Bodenmann (2008) and adapted to Turkish form by Eren Kurt and Akbas (2019). The DCI is a 37-item self-report questionnaire that measures the extent to which couples actively help each other during stressful times.…”
Section: Methodsmentioning
confidence: 99%
“…Dyadic Coping Inventory (DCI) This scale was developed originally by Bodenmann (2008) and adapted to Turkish form by Eren Kurt and Akbas (2019). The DCI is a 37-item self-report questionnaire that measures the extent to which couples actively help each other during stressful times.…”
Section: Methodsmentioning
confidence: 99%
“…The internal consistency coefficients (Croanbach's alpha) of the inventory were .92 for women and .93 for men in total score. The results of the confirmatory factor analysis conducted in the Turkish adaptation study of the inventory (Kurt & Akbaş, 2019) showed that individuals had an acceptable level of adjustment for self-coping (x 2 /sd=3.76, RMSEA=.06, CFI=.94, GFI=.95, SRMR=.04), spouse's perception of coping (x 2 /sd=4.50, RMSEA=.06, CFI=.95, GFI=.94, SRMR=.04) and perception of common coping (x 2 /sd=1.10, RMSEA=.01, CFI=1, GFI=.99, SRMR=.01). In the internal consistency analysis performed to determine the reliability of the inventory, Cronbach's alpha values ranged between .63 and .87 on the basis of sub-dimensions, and quasi-test values ranged between .63 and .85.…”
Section: Data Collection Toolsmentioning
confidence: 99%